“El parque de animales y el cerdo de dinero. Calcos y otras estrategias compensatorias en dos tipos de enseñanza bilingüe finés-español” - Judith Ansó Ros (Universidad Nebrija, 2022)
This article analyzes compensatory communicative strategies produced in Spanish by Spanish-Finnish bilingual students from two types of bilingual education. The data collection took place in two different periods: 29 schoolchildren aged between 8 and 10 participated to the first phase, while there were 24 in the second, aged between 10 and 12. Bilingual students use compensatory strategies such as reconceptualization, substitution and substitution plus, in order to fill lexical gaps. The study found substitution compensatory strategies, mainly as all purpose words, loans / code switching, and semantic approaches. Also circumlocutions and calques should be noticed, because of the high number of occurrences found. The strategies were analyzed according the total number, the number of produced words, to the evolution by degree, depending on the type of task and school provenance. The results show how the compensatory strategies decrease over time, that is, according to the grade studied. Likewise, the direct relationship between more competency and fewer strategies is clear.